Experimental Constraints on Homogenization of Plagioclase-Hosted Melt Inclusions From Plagioclase Ultraphyric Basalts - Lewis, Kristen R.; Ustunisik, Gokce K.; Nielsen, Roger L. (Frontiers in Earth Science, 2021)
Study of melt inclusions (MIs) is a commonly applied method for defining the composition of magmas present at depth prior to mixing, fractionation, and degassing. Our ability to use data from MIs is complicated by post-entrapment processes (PEP) that can modify their composition during transport and eruption. Many of the PEP can be reversed by heating the MIs to temperatures near those at which the MI and its host were formed. However, the process of reversing PEP by homogenization may introduce changes in MI compositions, making interpretation difficult. We present a series of low and high pressure homogenization experiments on plagioclase-hosted MIs from Plagioclase Ultraphyric Basalts (PUBs) designed to develop a methodology for recovering the composition at the time of entrapment of plagioclase-hosted MIs. These experiments included low pressure (1 bar) homogenization experiments conducted as a time series for 30 min, 4 hrs, 1 day, 4 days, and 8 days), and at 7.5 kbar for 2 and 4 days. The 7.5 kbar pressure used for the high pressure experiments was based on the CO2-based entrapment pressures determined from MI from this sample. Experiments run at low pressure and run times of 4 and 8 days exhibited compositional drift, most notably in the form of increasing MgO in MIs. This drift was not observed at 7.5 kbars or for the shorter run time 1 atm experiments. These results are consistent with a model where drift in composition with time is caused by crystal relaxation driven by the high internal pressure within the MI (the pressure at which the MI formed), together with the lower confining pressure during homogenization (1 bar). Therefore, MI homogenization will produce the least amount of drift if runs are made for short time periods (~30 minutes) or at the pressure of entrapment.